(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the incidence, causes and outcomes of revision cochlear implant surgeries in the Pakistan cochlear implant programme. Type: It is a retrospective descriptive study. Duration: Between August 2000 and January 2013. Setting: Pakistan cochlear implant programme, Lahore , Pakistan Patient and methods: A review of the medical data of the patients undergoing revision cochlear implantation was performed. Results: There were only 15 patients with revision cochlear implants out of 419 cochlear implants. Ten were male and 5 female. The time interval between the first and the second implant ranged from 1 to 7 years with a mean of 3 + 1.96 years. The causes for revision surgeries were electronic device failure in 11(73%) patients followed by trauma in 4(27%) patients. Conclusion: Cochlear implantation revision is a safe and effective procedure though revision itself is rarely required in these patients.